Neutral and adaptive genetic diversity in Neltuma alba (Leguminosae), an emblematic species of the Dry Chaco Forest - González, María Laura; Cosacov, Andrea; Lopez Lauenstein, Diego; Vega, Carmen Delcira; Teich, Ingrid; Bessega, Cecilia (Oxford University Press, 2025)
Dry forests, characterized by seasonal rainfall, are exposed to prolonged drought periods and high temperatures throughout the year, with the consequent restricted water availability. Organisms occurring in these environments must develop strategies to cope with drought stress; thus, local adaptations likely play a crucial role in these biomes. In South America, the largest contiguous xerophytic forests are found in the Chaco ecoregion, where Neltuma species (previously classified within Prosopis) play significant ecological and economic roles. However, no previous studies have assessed neutral and adaptive genetic variation across the distribution range of these species. This study evaluated the genetic patterns of geographically distant Neltuma alba populations, by comparing putative neutral simple sequence repeats (SSRs) with putative adaptive expressed sequence tags (EST-SSRs) derived from transcriptome sequencing, and their relationship with climatic factors. Our results revealed moderate genetic diversity and low genetic differentiation among populations. Notably, genetic structure varied with the type of marker, indicating different underlying evolutionary processes between them. The most important climatic gradient in the study area, defined by the east–west variation in precipitation and diurnal temperature range, could result in selective pressures on N. alba. This gradient might shape the genetic structure retrieved by the EST-SSRs and might be associated with leaf morphological patterns previously studied. The genetic diversity pattern of putative neutral markers was associated with geographic distances among populations but not with the climatic gradient. Our findings indicate that N. alba genetic diversity is influenced by two main factors: isolation by distance, whereby nearby populations tend to share more genetic diversity, and local adaptation, which arises from different selective pressures linked to the climatic gradient. Our results are discussed concerning their potential contribution to the management and conservation of this emblematic species of South American dry forests, which are facing landscape transformation and global climate change.